Protection of Tourism Rights for Persons with Disabilities - Made, Ni; R, Ibrahim; Ketut Supasti Dharmawan, Ni; Agung Istri Agung Ari Atu Dewi, Anak (International Journal of Educational Research & Social Sciences, 2023)
People with disabilities in Indonesia still experience difficulties in benefiting from the facilities at tourist attractions. The matter is not only related to tourist attractions but most of the supporting facilities for the implementation of tourism activities such as hotels, tour packages and adequate means of transportation are also difficult to find for persons with disabilities to support tourism activities. Motivated by these matters, there are two issues examined in the study: (1) how is the protection of persons with disabilities legally regulated in Indonesia? (2) How is the fulfillment of tourism rights for persons with disabilities in Indonesia implemented?. The method used in this study is empirical juridical research method. Data for the research were collected using field data collection technique and library data collection technique. The data were processed and analyzed qualitatively and presented in a qualitative descriptive method. The results of the study are: first, the essence of protecting the right to carry out tourism activities, especially in the provision of tourism accessibility rights for persons with disabilities is a form of Indonesian state’s obligation to provide respect, protection and respect for human rights for all its citizens without discrimination in order to realize welfare for persons with disabilities. This proportion is regulated in Law Number 8 of 2016 concerning Persons with Disabilities, Law Number 10 of 2009 concerning Tourism, and Government Regulation of the Republic of Indonesia No. 42 of 2020 concerning Accessibility to Settlements, Public Services, and Protection from Disasters for Persons with Disabilities. Second, the fulfillment of tourism rights for persons with disabilities in Indonesia has not been implemented properly. These obstacles are caused by the absence of legal certainty guarantees regarding regulations on the minimum standards of accessibility rights for persons with disabilities. As a result, in practice, there are still many public facilities supporting tourism activities that are inaccessible to persons with disabilities. To overcome these problems, it is necessary to have mandatory minimum standards that must be met so that persons with disabilities can enjoy traveling activities safely and comfortably.